Usaha Mikro Kecil Dan Menengah Kue Cucur Dua Saudara - Putri, Lydia Gustina; Febrianto, Edy; Ervina, Rahayu (Jurnal Kewirausahaan dan Bisnis, 2023)
Micro, Small and Medium Enterprises (MSM0Es) are productive economic enterprises that stand alone, which are carried out by individuals or business entities that are not subsidiaries or not branch companies that are owned, controlled or become part either directly or indirectly of medium or large businesses that are meet the small business criteria. One of the regional potentials that is often used as a business opportunity is regional food. Along with market demand, now many regional specialties are marketed in big cities, and not only limited to their area of ​​origin. This two brothers' cucur cake is one of the real proofs of the success of traditional food that many people already know both within the City and outside the City.